Decoding infantile hemangioma: cellular dynamics, molecular signals, and microenvironmental influences - Zhu, Zongdong; Jiang, Xiaoya; Wang, Fang; Zhao, Lijin; Song, Qinggao (Frontiers in Oncology, 2025)
Infantile hemangioma (IH), the most prevalent benign vascular tumor in neonates, typically appears several weeks after birth, undergoes rapid proliferation, and subsequently enters a prolonged phase of spontaneous involution. Recent advancements in molecular and cellular biology have revealed increasing evidence that the etiology and progression of IH arise from complex, multi-level interactions involving various factors. In this review, we examine the categorization of IH cells, analyze the pivotal roles of key molecular signaling pathways (e.g., VEGF, HIF, Notch), and elucidate the contributions of immune cells, hypoxia, the extracellular matrix, and exosome-mediated signaling within the tumor microenvironment to the angiogenic processes and regression of IH. These insights will enhance our understanding of IH pathogenesis, thereby laying the groundwork for the development of targeted therapeutic strategies.